Сказка о храброй Ясне и ветерке - Лиходед Виталий Григорьевич (Серия "Сказки", 2014)
Экземпляры: ф.5 (20160729) / Инвентарный номер: 48377 / Цена: 39.00 / Сис.шифр: Д / Авт.знак: Л 65 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6